Diagnóstico do potencial de internacionalização para o MERCOSUL: - Nunes, Jainara de Araujo (Universidade Federal do Tocantins, 2022)
The objective of this paper is to describe the implementation of a biopsy export plan to Mercosur from a cooperative located in the city of Xambioá - TO. The research is qualitative and descriptive, with data collection technique performed through semi-structured interviews. From the known data, the business modeling was elaborated by the Canvas model and the marketing potentialities were analyzed by the OKR Matrix. It was observed that the current conditions of the Cooperative's social media must be rethought and updated, as this is one of the main current portals for selling products to other countries. It was also found that there is the potential for internationalization of the Cooperative's products, due to the product coming from natural seeds, as well as a history of women leading the business of Xambiart.